Real time high frequency analysis system / Nor Zaheda Zainal - Zainal, Nor Zaheda
A Real Time High Frequency Analysis System provides a program to analyze High Frequency (HF) signal. This paper presents work carried out in developing a user friendly system to observe and analyze HF signal with MATLAB environment. The system consist two main parts; Offline HF analysis and real time (online) HF analysis. The sampling frequency used is 8000Hz and the channel bandwidth is 3 kHz. HF signal is the radio spectrum with frequencies range between 3 to 30 MHz. HF is widely used in long distance communication and very popular among amateur radio operators and military communication [1].